Mental health among outpatient reproductive health care providers during the US COVID-19 epidemic - Alison B. Comfort; Paul J. Krezanoski; Lavanya Rao; Alison El Ayadi; Alexander C. Tsai; Suzan Goodman; Cynthia C. Harper (BMC, 2021)
Abstract Introduction Both inpatient and outpatient providers may be at increased risk of stress, anxiety and depression from their roles as health providers during the COVID-19 epidemic. This study explores how the US COVID-19 epidemic has increased feelings of stress, anxiety and depression among outpatient reproductive health providers. Methods We conducted a survey with open-ended responses among outpatient reproductive health providers across the U.S. engaged in contraceptive care to collect data on their experiences with stress, anxiety and depression during the COVID-19 epidemic. The study population included physicians, nurses, social workers, and other health professions [n = 288]. Data were collected from April 21st-June 24th 2020. We used content analysis of free text responses among providers reporting increased stress, anxiety or depression. Results Two-thirds (184) of providers reported increased stress and one-third (96) reported increased anxiety or depression related to care provision during the COVID-19 epidemic. The major sources of stress, anxiety and depression were due to patient care, worry about becoming infected or infecting family members, work- and home-related concerns, experiencing provider burnout, and fear of the unknown. Concerns about quality of patient care, providers' changing responsibilities, lack of personal protective equipment, and difficulty coping with co-worker illness and absence all contributed to provider stress and anxiety. Worries about unemployment and childcare responsibilities were also highlighted. Providers attributed their stress, anxiety or depression to feeling overwhelmed, being unable to focus, lacking sleep, and worrying about the unknown. Conclusions US outpatient providers are experiencing significant stress, anxiety, and depression during the US COVID-19 epidemic. Policy and programmatic responses are urgently needed to address the widespread adverse mental health consequences of this epidemic on outpatient providers, including reproductive health providers, across the US. Plan English summary Both inpatient and outpatient providers may be at increased risk of stress, anxiety and depression from their roles as health providers during the COVID-19 epidemic. This study explores how the US COVID-19 epidemic has increased feelings of stress, anxiety and depression among outpatient reproductive health providers across the US. We conducted a survey from April 21st to June 24th, 2020 among outpatient reproductive health providers, including physicians, nurses, social workers and other health professions. We asked open-ended questions to understand why providers reported increased stress, anxiety and/or depression. Two-thirds (184) of providers reported increased stress and one-third (96) reported increased anxiety or depression from care provision during the COVID-19 epidemic. Major sources of stress, anxiety and depression were due to patient care, worry about becoming infected or infecting family members, work- and home-related concerns, experiencing provider burnout, and fear of the unknown. Concerns about quality of patient care, providers' changing responsibilities, lack of personal protective equipment, and difficulty coping with co-worker illness and absence all contributed to provider stress and anxiety. Worries about unemployment and childcare responsibilities were also highlighted. Providers attributed their stress, anxiety or depression to feeling overwhelmed, being unable to focus, lacking sleep, and worrying about the unknown. This study highlights that US outpatient reproductive health providers are experiencing significant stress, anxiety, and depression during the US COVID-19 epidemic. Policy and programmatic responses are urgently needed to address the widespread adverse mental health consequences of this epidemic on outpatient providers, including reproductive health providers, across the US.